Factors influencing implementing inclusive education in Chris Hani East district, South Africa - Thanduxolo Nomtshongwana; Manyakaza Aviwe; Buka Andria Mqondiso (International Journal of Studies in Inclusive Education)
This paper investigates how inadequate teacher training can influence the implementation of inclusive education. It explores how insufficient preparation in inclusive pedagogy, differentiated instruction, and identification of diverse learning needs hinder teachers' ability to effectively support all students in regular classrooms. A purposive sampling method was used to select 20 participants with substantial knowledge and relevant experience regarding challenges posed by inadequate teacher training in implementing inclusive education. Data were gathered through semi-structured interviews with educators from diverse backgrounds across the various districts of Chris Hani East. T thematic results revealed that inadequate teacher training adversely affects the academic and social-emotional outcomes of students with disabilities in inclusive classrooms, leading to lower academic performance and skill development, diminished self-esteem and confidence, heightened social isolation and bullying, and the emergence of negative behaviours as coping strategies. It recommends that teacher training focuses on practical strategies and collaboration between general and special education teachers. Mentorship programmes and regular workshops can enhance teacher support. A positive school culture, peer support, and social-emotional learning programmes can help reduce bullying and isolation. Involving parents, implementing clear anti-bullying policies, and regularly assessing programmes based on feedback will create a safe and inclusive environment for all students.